Analisis Rasio Likuiditas Pada Laporan Keuangan PT. Bank Negara Indonesia (Persero) Tbk Tahun 2019-2023 - Siti Rohizah; Jeniper Indah Pandiangan; Sandy Mukti Ali; Renny Oktafia (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
Bank Negara Indonesia (BNI) is one of the largest banks in Indonesia, which if you look at it has experienced significant development, especially in terms of assets and income, which are benchmarks for its financial performance. Financial ratio analysis, especially liquidity ratios, is an important part of measuring a bank's ability to pay short-term obligations. Liquidity ratios, such as Current Ratio, Cash Ratio, Loan to Deposit Ratio, and Loan to Asset Ratio, provide an overview of the bank's financial health. Through quantitative methods and research literature, we want to know how much Bank Negara Indonesia's liquidity ratio has developed from 2019 to 2023. From the analysis of this ratio, it can be concluded that Bank Negara Indonesia has quite good liquidity during the 2019 to 2013 period, which directly means that Bank Negara Indonesia has a good ability to pay its short-term obligations.